Hypertension in Guatemala's Public Primary Care System: A Needs Assessment Using the Health System Building Blocks Framework - Meredith P. Fort; William Mundo; Alejandra Paniagua-Avila; Sayra Cardona; Juan Carlos Figueroa; Diego Hernández-Galdamez; Kristyne Mansilla; Ana Peralta-García; Dina Roche; Eduardo Alberto Palacios; Russell E. Glasgow; Pablo Gulayin; et al. (BMC, 2021)
Abstract Background Uncontrolled hypertension represents a substantial and growing burden in Guatemala and other low and middle-income countries. As a part of the formative phase of an implementation research study, we conducted a needs assessment to define short- and long-term needs and opportunities for hypertension services within the public health system. Methods We conducted a multi-method, multi-level assessment of needs related to hypertension within Guatemala's public system using the World Health Organization's health system building blocks framework. We conducted semi-structured interviews with stakeholders at national (n = 17), departmental (n = 7), district (n = 25), and community (n = 30) levels and focus groups with patients (3) and frontline auxiliary nurses (3). We visited and captured data about infrastructure, accessibility, human resources, reporting, medications and supplies at 124 health posts and 53 health centers in five departments of Guatemala. We conducted a thematic analysis of transcribed interviews and focus group discussions supported by matrix analysis. We summarized quantitative data observed during visits to health posts and centers. Results Major challenges for hypertension service delivery included: gaps in infrastructure, insufficient staffing and high turnover, limited training, inconsistent supply of medications, lack of reporting, low prioritization of hypertension, and a low level of funding in the public health system overall. Key opportunities included: prior experience caring for patients with chronic conditions, eagerness from providers to learn, and interest from patients to be involved in managing their health. The 5 departments differ in population served per health facility, accessibility, and staffing. All but 7 health posts had basic infrastructure in place. Enalapril was available in 74% of health posts whereas hydrochlorothiazide was available in only 1 of the 124 health posts. With the exception of one department, over 90% of health posts had a blood pressure monitor. Conclusions This multi-level multi-method needs assessment using the building blocks framework highlights contextual factors in Guatemala's public health system that have been important in informing the implementation of a hypertension control trial. Long-term needs that are not addressed within the scope of this study will be important to address to enable sustained implementation and scale-up of the hypertension control approach.